(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the impact of gadget use on the learning concentration of students at the Balikpapan College of Economics. The research method used is quantitative with a survey design. The sample consisted of 150 students selected by purposive sampling from various departments. The research instrument was a questionnaire that measured the intensity of gadget use, types of gadget activities (academic and non-academic), and level of learning concentration. Data analysis was performed using multiple linear regression. The research instrument was a questionnaire that measured the intensity of gadget use, types of gadget activities (academic and non-academic), and the level of concentration in learning. Data analysis was performed using multiple linear regression and Pearson Product Moment’s correlation. The results of the study showed that there was a significant negative effect between on-academic gadget use and concentration in learning. Conversely, the use of gadgets for academic purposes showed a positive correlation, although the effect was weaker than the negative effect of non-academic use. It is recommended that students manage their gadget usage time and that educational institutions provide education on effective gadget usage so that learning concentration can be improved.